INVESTIGATION OF SOME FIXED POINT THEOREMS IN HYPERBOLIC SPACES FOR A THREE STEP ITERATION PROCESS - Atalan, Yunus; Karakaya, Vatan (KANGWON-KYUNGKI MATHEMATICAL SOC, 2019)
In the present paper, we investigate the convergence, equivalence of convergence, rate of convergence and data dependence results using a three step iteration process for mappings satisfying certain contractive condition in hyperbolic spaces. Also we give non-trivial examples for the rate of convergence and data dependence results to show effciency of three step iteration process. The results obtained in this paper may be interpreted as a refinement and improvement of the previously known results.
Keywords: iteration process; contractive type operators; hyperbolic spaces; BANACH-SPACES; CONVERGENCE; GEOMETRY; MAPPINGS; STABILITY; PAIR; Mathematics